Interpersonal relationships and work values of elementary school teachers and administrators in Region XII - Pendaliday, Bologiong P.
This study looked into the work values and interpersonal relationships of 234 public elementary school teachers and 24 principals and the personal and socio-demographic characteristics and school factors which can predict these. Kendall rank partial correlation, Pearson correlation technique, chi-square test, and stepwise regression analysis were used. The expressed work values and interpersonal relationships of teachers and principals did not differ. Generally, both groups tend to attach great importance to all identified work values such as achievement, competence, recognition, chance for experience and development, etc. Educational attainment is positively related to work values and interpersonal relations.